Digital technologies for solar photovoltaic systems : from general to rural and remote installations - Motahhir, Saad (IET energy engineering series, 2022)
The rising share of photovoltaic (PV) energy requires sophisticated digital techniques for control, monitoring and integration with the grid. In remote areas, where no trained personnel might be nearby to intervene, such technologies are vital to ensure reliability and power quality, and to harness the solar potential of these locations. Moreover, tracking is necessary for moveable systems. Digital technologies can be used to enable and augment the use of PV energy in the grid, as well as for desalination, water pumping and hydrolysis. Digital Technologies for Solar Photovoltaic Systems: From general to rural and remote installations focuses on the latest research and developments in PV energy system operation and integration. It provides extensive coverage of R&D to overcome critical limitations to the use of remote PV systems. Chapters cover phase-shifting transformers, grid-connected PV micro-inverter, distribution automation, PV powered water pumping, maximum power point tracking and solar tracking, soiling effects and measurement, cleaning methods, IoT based PV module cooling and cleaning, control of energy storage, and energy management. This book is a highly useful reference guide for researchers, designers, operators, and experts involved with PV systems, as well as for graduate students.